Analysis of Students' Mathematical Problem-Solving Ability on Trigonometry - Alfian Adi Perkasa; Dwi Astuti (Universitas Sarjanawiyata Tamansiswa, 2022)
This investigation aims to examine problem-solving ability (PSA) in Polya's problem-solving phases in the material of sine and cosine number and difference. This study used the descriptive qualitative research method. This study looked at 33 students in Class XI MIPA 5 from SMA Negeri 2 Bantul. Data was collected using written tests and interviews. The written test in this study takes the form of a two-point description question. The study's findings were used to calculate the mathematics PSA of students in class XI MIPA 5 at SMA Negeri 2. In mathematics, the average percentage of students who meet the low requirement is 59.72 percent. Furthermore, children with high expectations can thoroughly, meticulously, and systematically solve difficulties. Understanding the problem remains a struggle for pupils who reach intermediate standards and have yet to complete the problem's solution. Meanwhile, students who scored low on the criteria had trouble understanding the problem and were unable to solve it using the prepared plans, as well as students who were unable to double-check the response and complete the solution to the problem that had been solved.